Comparison of two-prototype near-horizontal Drain Water Heat Recovery units on the basis of effectiveness. (15th April 2019) - Pochwat, Kamil; Kordana, Sabina; Starzec, Mariusz; Słyś, Daniel
Abstract: Recovery of energy carried by greywater is possible, for instance, through application of Drain Water Heat Recovery (DWHR) units at the drain water outlet from a shower unit. This paper reports results of a study concerning assessment of rationale behind the use of two different horizontal DWHR units. The analysis, carried out in laboratory conditions proved that equipping of the unit with properly shaped baffles can significantly increase its effectiveness. The effect was observed for all flow rates and device body bottom slopes adopted for the analysis. The paper points out the effect of difference of temperatures between the preheated water and the greywater giving up the heat. The effect turned out to be small in case of the compared devices. Results presented in the paper are of a practical value and can be used as guidelines for designers and potential investors. Highlights: Two prototype near-horizontal DWHR units were examined in laboratory conditions. Equipping the near-horizontal DWHR unit with baffles increases its efficiency. The highest efficiency is obtained when DWHR units are connected in parallel. The effect of flow rates was more significant than that of other examined parameters. The developed DWHR unit is designed for existing residential buildings.